Kualitas Citra Radiografi Berdasarkan Variasi Jeda Waktu Pembacaan Citra pada Computed Radiography - Dartini Dartini; Florentina Yunita Wulandari; Akhmad Haris Sulistiyadi (Jurnal Imejing Diagnostik (JImeD), 2016)
Background: Computed Radiography (CR) is imaging processor to digitize an image using imaging plate. Imaging plate can store latent image and should be read as soon as possible to avoid the loss of image quality. The longer storage time the lower image quality. This study aimed to determine the image quality in various image reading time delay.Methods: This iresearch was quantitative research with experimental approach. 5 images were acquired using step wedge as an object with same exposure factors. The imaging plates were read in five different image reading time delay variations (no-delay, 2 hours, 4 hours, 6 hours, and 8 hours after eksposure). Contrast and density of each image were measured using lgM and densitometer. Data were analyzed by comparing lgM, density, and contrast of each image.Result: The result showed that there were difference value in density, contrast, and lgM among no-delay, 2 hours, 4 hours, 6 hours, and 8 hours after eksposure images respectively. The average density were 0,701; 0,776; 0,772; 0,798; 0,791. The image contrast were 0,88; 1,09; 0,88; 1,06; 1,02. The lgM value were 2,42; 2,24; 2,21; 2,20; 2,19.Conclusion: The image quality was decreased over reading time delay, the longer reading time delay the lower image quality. To obtain the best image quality, the imaging plate should be read as soon as possible.